Effect of sanitizers and storage environment on shelf-life and quality of pointed gourd (Trichosanthes dioica) - KOLEY, TANMAY KUMAR; ASREY, RAM; SAMUEL, D V K (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during 2006 to study the effect of sodium hypochlorite (NaClO), potassium metabisulphite (KMS) and edible carnauba wax (Carnauba leaf extract) on physiological activities, quality parameters and shelf-life of pointed gourd (Trichosanthes dioica Roxb.) under ambient storage conditions (28Â°C temperature and 85% relative humidity). Fruits treated with 100 mg/litre NaClO + 500 mg/litre KMS + 1:10 wax emulsion (T2) effectively retarded respiration rate, phyliological loss of weight, retained higher hue angle and lower chroma value of the fruits throughout the 5 days storage period. Firm pulp texture and lower seed hardness (desirable characters) were also retained in T2 treated fruits, however, higher concentrations of NaClO and KMS resulted in undesirable. Chlorophyll retention in pointed gourd skin tissues was 2.0 times higher in T2 treated fruits than that of 1:10 wax emulsion (T1). It also lowered the sugar and carotenoid development in fruits during storage period. Pectin methyl easterase activity was delayed (20% less) in fruits under T2 treatment compared to T1. Irrespective of treatments, total sugars content was increased in stored fruits. Pointed gourd fruits showed the non-climacteric type behaviour since no ethylene was detected both in treated and un-treated fruits up to 5 days of storage period. However, fruit skin yellowing was observed with the advancement of storage duration. Â